Disparities in the characteristics and outcomes of patients hospitalized with acute decompensated heart failure admitted to internal medicine and cardiology departments: a single‐centre, retrospective cohort study. (24th November 2020) - Maymon, Shiri Lea; Moravsky, Gil; Marcus, Gil; Shuvy, Mony; Pereg, David; Epstein, Danny; Litovchik, Ilya; Fuchs, Shmuel; Minha, Sa'ar
Abstract: Aims: Efforts are constantly made to decrease the rates of readmission after acute decompensated heart failure (ADHF). ADHF admissions to internal medicine departments (IMD) were previously associated with higher risk for readmission compared with those admitted to cardiology departments (CD). It is unknown if the earlier still applies after recent advancement in care over the last decade. This contemporary cohort compares characteristics and outcomes of ADHF patients admitted to IMD with those admitted to CD. Methods and results: The data for this single‐centre, retrospective study utilized a cohort of 8332 ADHF patients admitted between 2007 and 2017. We compared patients' baseline characteristics and clinical and laboratory indices of patients admitted to CD and IMD with the outcome defined as 30 day readmission rate. In comparison with those admitted to CD, patients admitted to IMD (89.5% of patients) were older (79 [70–86] vs. 69 [60–78] years; P < 0.001) and had a higher incidence of co‐morbidities and a higher ejection fraction. Readmission rates at 30 days were significantly lower in patients admitted to CD (15.9% vs. 19.6%; P = 0.01). Conflicting results of three statistical models failed to associate between the admitting department and 30 day readmission (odds ratio for 30 day readmission in CD: forced and backward stepwise logistic regression 0.8, 95% confidence interval 0.65–0.97, P = 0.02; stabilized inverse probability weights model odds ratio 1.0, confidence interval 0.75–1.37, P = 0.96). Conclusions: This contemporary analysis of ADHF patient cohort demonstrates significant differences in the characteristics and outcomes of patients admitted to IMD and CD. Thus, focusing strategies for readmission prevention in patients admitted to IMD may be beneficial.